A comparison of sustainable business models between goods and service industries: similarities and differences. (2016) - HÁ¸gevold, Nils M.; Svensson, Göran; Padin, Carmen; Santos, Maria Dos
The objective is to describe and compare two sustainable business models, one in a manufacturing industry and the other in a hospitality industry. Data was gathered from multiple sources in two case studies, including secondary data, company records, internet information, face-to-face interviews and on-site observations. Transcriptions were returned to interviewees for clarification, enhanced accuracy, and approval. The researchers remained open and receptive to emerging insights, contributing to the comparison between industries. The content analysis of transcribed interviews and other sources of data revealed a number of aspects, some similar and some different, between the sustainable business models explored. The sustainable business models assessed in this study thus consist of both similar and different elements. A differentiator between sustainable business models is whether the core offer to customers in the market is predominantly service- or goods-oriented. Further studies on common denominators and distinguishing criteria between sustainable business models would be valuable to both researchers and practitioners.